Assessment of health care quality in the tertiary level pediatric hospitals in Serbia - Kuburović Nina; Đuričić Slaviša M.; Nešković Anđelija; Dedić Velimir; Kuburović Vladimir (Vojnosanitetski Pregled)
Background/Aim. It is necessary to improve the quality of health care for children. Assessment data would provide new insights into better treatment outcomes. The aim of this descriptive study was to estimate and to compare applied quality indicators in five pediatric inpatient tertiary level institutions in Serbia during the period from January 1st to December 31st 2008. Methods. Quality data and indicators were collected in the Institute for Public Health of Serbia “Dr. Milan Jovanović Batut”. Descriptive statistics and chisquare test were used for data analysis. Results. The average length of stay (ALOS) in pediatric departments was 7.51 ± 1.30 days (5.88-8.91 days). In the same period, ALOS in pediatric surgery departments was 5.85 ± 1.50 days (3.58-7.57 days). The average number of nurses per occupied bed was 0.76 ± 0.20 and 1.09 ± 0.36 in pediatric and in pediatric surgery departments, respectively. The number of operated patients per surgeon was in the range 51.0-160.5. The annual case fatality rate in pediatric departments was estimated to 0.72% ± 0.20%, whereas in pediatric surgery departments it was 0.34% ± 0.25%. The autopsy rate was estimated to 0.00%-63.16% in pediatric departments, and 37.14%-80.00% in pediatric surgery departments. There was statistically significant difference among the five hospitals regarding the following indicators of quality of work: total annual mortality rate of patients, autopsy rate, number of rate of patients, autopsy rate, number of patients referred to other institutions, both in pediatric and pediatric surgery departments. Conclusion. There is a significant difference among the five hospitals regarding indicators of quality of work. Obligatory set of quality indicators on the basis of legislative acts are the indicators of general quality of work in hospital. It is necessary to establish specific pediatric quality indicators and to define national standards related to these indicators.